Comparison of corn and grain sorghum dried distillers grains as protein supplements for growing beef heifers - Harborth, K.W.; Marston, T.T.; Llewellyn, Donald A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An experiment was conducted to determine if corn and grain sorghum dried distillers grains could be effective protein supplements for growing beef replacement heifers. Crossbred heifers (n=77) were individually fed 6 lb/heifer daily (dry matter basis) of supplements containing 20% crude protein. The three supplements compared were: 1) 50% cracked corn, 25% soybean meal, and 25% ground grain sorghum; 2) 50% cracked corn and 50% corn distillers grains with solubles; and 3) 50% cracked corn, 31% sorghum distillers grains with solubles, and 19% ground grain sorghum. Heifers grazed a common native- grass pasture and had free-choice access to smooth broom hay in round bale feeders. During the last week of the trial, heifers (n=4) from each supplement were used to determine diet digestibility. Although there were no differences in weight gain or total diet digestibility, dry matter intake as a percentage of body weight was less for heifers receiving supplements containing dried distillers grains from either corn or grain sorghum. Our data indicate that producers can expect similar growth performance, regardless of the grain source of dried distillers grains used to formulate a 20% crude protein supplement fed at about 1% of body weight daily.
Keywords: Beef; Corn; Grain sorghum; Dried distillers grains; Heifers